Effect of different impression materials and techniques on the dimensional accuracy of implant definitive casts - Behnaz Ebadian; Mansor Rismanchian; Badrosadat Dastgheib; Farshad Bajoghli (Wolters Kluwer Medknow Publications, 2015)
Background: Different factors such as impression techniques and materials can affect the passive fit between the superstructure and implant. The aim of this study was to determine the effect of different impression materials and techniques on the dimensional accuracy of implant definitive casts. Materials and Methods: Four internal hex implants (Biohorizons Ψ4 mm) were placed on a metal maxillary model perpendicular to the horizontal plane in maxillary lateral incisors, right canine and left first premolar areas. Three impression techniques including open tray, closed tray using ball top screw abutments and closed tray using short impression copings and two impression materials (polyether and polyvinyl siloxane) were evaluated (n = 60). The changes in distances between implant analogues in mediolateral (x) and anteroposterior (y) directions and analogue angles in x/z and y/z directions in the horizontal plane on the definitive casts were measured by coordinate measuring machine. The data were analyzed by multivariate two-way analysis of variance and one sample t-test (α = 0.05). Results: No statistical significant differences were observed between different impression techniques and materials. However, deviation and distortion of definitive casts had a significant difference with the master model when short impression copings and polyvinyl siloxane impression material were used (P < 0.05). In open tray technique, there was a significant difference in the rotation of analogs compared with the master model with both impression materials (P < 0.05). Conclusion: There was no difference between open and closed tray impression techniques; however, less distortion and deviation were observed in the open tray technique. In the closed tray impression technique, ball top screw was more accurate than short impression copings.